THE INFLUENCE OF ADOBE FLASH-BASED LEARNING MEDIA ON INTEREST IN LEARNING MATHEMATICS - Deiby Neltje Fransiska Tiwow; Henny Nikolin Tambingon; Viktory Nicodemus Joufree Rotty; Edino Ayub Lomban; Navel Oktaviandy Mangelep (CV. Pusdikra Mitra Jaya, 2022)
The study aimed to determine the effect of Adobe Flash-based learning media on interest in learning mathematics. The type of research is Quasi-Experimental Quantitative with the